IMPLEMENTASI MODEL PEMBELAJARAN PBL MELALUI PENDEKATAN TPACK PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Kardiana Zendha Avalentina; Dyah Worowirastri Ekowati; Rizki Juni Sulistyawati (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This research was conducted to improve the learning outcomes of grade 1 students by using the PBL learning model through the TPACK approach in Pancasila Education lessons. Method: The type of research used was PTK which was carried out over 2 cycles. see student learning outcomes after using the PBL learning model through the TPAC approach. An increase in learning outcomes at the second meeting was achieved, getting a percentage of 92.50% with the "very good" criteria, in teacher activities getting a percentage of 89.50% with the "very good" criteria, while in student learning outcomes getting a percentage of 93.50% with the criteria " finished." So this model can be used in the classroom learning process.